2020
DOI: 10.3389/fncel.2020.542552
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long Non-coding RNA LINC00320 Inhibits Tumorigenicity of Glioma Cells and Angiogenesis Through Downregulation of NFKB1-Mediated AQP9

Abstract: The inhibitory effect of long intergenic non-coding RNA 00320 (LINC00320) in glioma cell proliferation has been proposed in a recent study. However, the mechanisms by which LINC00320 regulate aquaporin 9 (AQP9) in glioma require further exploration. Hence, this study aims to investigate effects of LINC00320 on tumorigenicity of glioma cells and angiogenesis of microvascular endothelial cells (MVECs). Expression of LINC00320 and AQP9 in glioma tissues and cells was measured by reverse transcription–quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…LncRNA PAXIP1-AS1 was identified to boost migration and angiogenesis of glioma by upregulating ETS1-midiated KIF14 expression [ 36 ]. Aside from the pro-angiogenetic potential, Chang et al found lncRNA LINC00320 suppressed tumourigenicity of glioma and angiogenesis through reduction of NFKB1-regulated AQP9 [ 37 ]. A growing body of ARlncRs not only provided therapeutic targets, but were also promising for diagnosis and prognosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA PAXIP1-AS1 was identified to boost migration and angiogenesis of glioma by upregulating ETS1-midiated KIF14 expression [ 36 ]. Aside from the pro-angiogenetic potential, Chang et al found lncRNA LINC00320 suppressed tumourigenicity of glioma and angiogenesis through reduction of NFKB1-regulated AQP9 [ 37 ]. A growing body of ARlncRs not only provided therapeutic targets, but were also promising for diagnosis and prognosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA PAXIP1-AS1 was identi ed to boost migration and angiogenesis of glioma by upregulating ETS1midiated KIF14 expression 36 . Aside from the pro-angiogenetic potential, Chang et al found lncRNA LINC00320 suppressed tumourigenicity of glioma and angiogenesis through reduction of NFKB1-regulated AQP9 37 . A growing body of ARlncRs not only provided therapeutic targets, but were also promising for diagnosis and prognosis evaluation.…”
Section: Discussionmentioning
confidence: 99%
“… 96 Analysis of database GSE104291 indicated that there were 91 genes with high expression and 268 genes with low expression. 73 lncRNA SLC26A4-AS1 was meaningly downregulated in glioma tissues and cells. Upregulation of SLC26A4-AS1 in U251 and SHG44 cells inhibited the proliferation, migration, and angiogenesis of U251 and SHG44 cells.…”
Section: Correlation Between Lncrnas and Angiogenesis In Cancermentioning
confidence: 96%
“… 72 However, LINC00320 inhibited AQP9 expression by recruiting NFKB1 to the promoter region of AQP9, thus acting as a tumor suppressor gene in glioma ( Figure 2 F). 73 Osteosarcoma is a common and highly malignant bone tumor, mostly occurring in adolescents. lncRNA TUG1 was overexpressed in osteosarcoma tissues and is associated with poor prognosis of patients.…”
Section: Correlation Between Lncrnas and Angiogenesis In Cancermentioning
confidence: 99%